Boundary discontinuous Fourier analysis of thick cross-ply clamped plates - Oktem, Ahmet Sinan; Chaudhuri, Reaz A. (ELSEVIER SCI LTD, 2008)
A new analytical solution to the problem of deformation of a finite-dimensional general cross-ply thick rectangular plate, modeled using a higher order shear deformation theory (HSDT), is presented. A solution methodology, based on a boundary-discontinuous generalized double Fourier series approach, is used to solve a system of five highly coupled linear partial differential equations, generated by the HSDT-based laminated plate analysis, with the C3-type clamped boundary condition prescribed at all four edges. The numerical accuracy of the solution is ascertained by studying the convergence characteristics of deflections and moments of a cross-ply plate. The primary focus of the present study is to investigate the effect of end clamping on the response of a thick laminated plate, while keeping the in-plane end constraints unaltered. Important numerical results presented include sensitivity of the predicted response quantities of interest to lamination, material property, thickness effects and end clamping as well as their interactions. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: thick laminate; higher order shear deformation theory; cross-ply; analytical solution; boundary discontinuous double Fourier series; boundary constraints; clamped; HIGHER-ORDER THEORY; MODERATELY THICK; FREQUENCY-RESPONSE; FREE-VIBRATION; CONSTRAINT; DEFORMATION; SHELL; Mechanics; Materials Science